Resposta de cultivares de trigo ao nitrogênio com e sem tratamento fúngico - Filho, Marcelo C. M. Teixeira [UNESP]; Buzetti, Salatiér [UNESP]; Arf, Orivaldo [UNESP]; De Alvarez, Rita C. F.; Maeda, Alexandra S.; De Sá, Marco E. [UNESP] (Revista Brasileira de Ciencias Agrarias, 2012)
The fungicide can enhance response of nitrogen fertilization on wheat crop, since the application of higher N rates can provide better conditions for the development of some diseases. The present study investigated the effects of different nitrogen doses and fungicide application in preventive character on the yield of two cultivars of wheat irrigated, in Savannah conditions. The experiment was conducted in Selvíria - MS, in a Distrophic Red Latosol (Typic Haplustox). Treatments were arranged in a randomized block design, in a 4x2x2 factorial scheme: four N rates (0, 60, 120 and 180 kg ha-1), topdressing at the early boot stage as urea, two wheat cultivars (IAC 24 and IAC 370), and with and without fungicide application (Tebuconazole and Triciclazol), with four replications. The cultivars IAC 24 and IAC 370 present similar grain yield. The increase of N doses influences the mass hectoliter negatively and the leaf N content and number of ears per m2 positively. The increment of N doses increase the grain yield up to dose of 116 kg ha -1 of N, regardless of cultivar and of the fungicide application in preventive character, due to non occurrence of diseases in the experiment.
Response of wheat cultivars to nitrogen with and without fungal treatment
Keywords: Grain yield; Irrigation by sprinkler; Savannah; Triticum aestivum L.; Urea; Triticum aestivum